2008
DOI: 10.1007/s10329-008-0080-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive parameters over a 37-year period of free-ranging female Borneo orangutans at Sepilok Orangutan Rehabilitation Centre

Abstract: We analysed the reproductive parameters of free-ranging female orangutans at Sepilok Orangutan Rehabilitation Centre (SORC) on Borneo Island, Sabah, Malaysia. Fourteen adult females produced 28 offspring in total between 1967 and 2004. The average censored interbirth interval (IBI) (i.e. offspring was still alive when mother produced a next offspring) was 6 years. This was shorter than censored IBIs reported in the wild but similar to IBIs reported for those in captivity. The nonparametric survival analysis (K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…The rate of infant mortality at Camp Leakey was significantly lower than that at Sepilok (Kuze et al 2008). Kuze et al (2008) speculate that their extremely high (58 %) observed rate of infant mortality had two possible causes: (1) human rearing causing poor infant care skills, and (2) increased sociality due to provisioning leading to increased aggression and disease transmission.…”
Section: Infant Mortalitymentioning
confidence: 92%
See 4 more Smart Citations
“…The rate of infant mortality at Camp Leakey was significantly lower than that at Sepilok (Kuze et al 2008). Kuze et al (2008) speculate that their extremely high (58 %) observed rate of infant mortality had two possible causes: (1) human rearing causing poor infant care skills, and (2) increased sociality due to provisioning leading to increased aggression and disease transmission.…”
Section: Infant Mortalitymentioning
confidence: 92%
“…The first-generation mothers' mean age at first reproduction (mean Gen1 = 14.2, n Gen1 = 11, SD Gen1 = 1.17, range Gen1 = 12-16) was significantly older than that of the secondgeneration mothers (mean Gen2 = 12.1, n Gen2 = 8, SD Gen2 = 0.99, range Gen2 = 11-13) (Mann-Whitney U test; n Gen1 = 11, n Gen2 = 8, U = 6.5, p \ 0.001). Ages at first reproduction of the first-and second-generation Camp Leakey mothers were each compared to two other orangutan populations for which published data sets are available: Sepilok Orangutan Rehabilitation Center (''Sepilok,' ' Kuze et al 2008) and wild orangutans at Tanjung Puting National Park (''Wild TPNP,'' Galdikas, personal observation as published in Tilson et al 1993). The distribution of age at first reproduction varied significantly across populations (CL Gen 1-Sepilok-Wild TPNP, independent-samples Kruskal-Wallis test, p \ 0.005; CL Gen 2-Sepilok-Wild TPNP, independent-samples KruskalWallis test, p \ 0.05).…”
Section: Age At First Reproductionmentioning
confidence: 99%
See 3 more Smart Citations